Human Anatomy Lab Manual - Wilk-Blaszczak, Malgosia; Open Textbook Library (Open Textbook Library, 2018)
This is a lab manual for a college-level human anatomy course. Mastery of anatomy requires a fair amount of memorization and recall skills. The activities in this manual encourage students to engage with new vocabulary in many ways, including grouping key terms, matching terms to structures, recalling definitions, and written exercises. Most of the activities in this manual utilize anatomical models, and several dissections of animal tissues and histological examinations are also included. Each unit includes both pre- and post-lab questions and six lab exercises designed for a classroom where students move from station to station. The vocabulary terms used in each unit are listed at the end of the manual and serve as a checklist for practicals.
Lab 1: Anatomical Language -- Lab 2: Bones and Bone Markings -- Lab 3: Spinal Cord and Spinal Nerves -- Lab 4: Brain and Cranial Nerves -- Lab 5: Special Senses -- Lab 6: Respiratory System -- Lab 7: The Cardiovascular system -- Lab 8: Digestive System -- Lab 9: Urinary and Reproductive Systems -- Lab 10: The Muscular and Integumentary systems
In English.
Description based on print resource
Keywords: Biology -- Textbooks